Strategic Leadership of Administrators and Performance on Child Development Center’s Standard Under the Municipality in Nonthaburi Province - Phonphahol, Suneekorn; Rattanasiraprapha, Assoc.Prof.Dr.Nuchnara (Journal of Dhamma for Life, 2025)
The purposes of this research were to determine 1) Strategic leadership of administrators of child development center’s standard under the municipality in Nonthaburi province, and 3) the relationship between strategic leadership of administrators and performance on child development center’s standard under the municipality in Nonthaburi province. The study sample comprised 59 child development centers under the municipality, with a total of 118 respondents, including center heads and teachers. The research employed a questionnaire as the primary instrument, measuring strategic leadership based on the framework of Michael A. Hitt, R. Duane Ireland, and Robert E. Hoskisson, and performance standards defined by the Office of the Education Council. Data analysis utilized descriptive and inferential statistics, including frequency, percentage, mean, standard deviation, and Pearson’s product-moment correlation coefficient. Key findings were as follows: The strategic leadership of administrators was rated at a high level overall and across individual dimensions. The dimensions were ranked, from highest to lowest mean, as follows: Determining Strategic Direction, Emphasizing Ethical Practices, Sustaining an Effective Organizational Culture, Establishing Balanced Organizational Controls, and Effectively Managing the Firm’s Resource Portfolio. The performance of child development centers was rated at the highest level overall and across individual aspects. The aspects were ranked, from highest to lowest mean, as follows: Systematic Management, Promotion of Family and Community Involvement, Management to Promote Health and Learning, Safety Environment Management, and Personnel Management. A statistically significant positive correlation (at the 0.01 level) was found between administrators' strategic leadership and the performance of child development centers. These findings underscore the critical role of strategic leadership in enhancing the performance of child development centers under municipal administration.